Blinders, Blunders, and Wars What America and China Can Learn - Gompert, David C. 1945- (RAND Corporation, 2014)
The history of wars caused by misjudgments, from Napoleon's invasion of Russia to America's invasion of Iraq, reveals that leaders relied on cognitive models that were seriously at odds with objective reality. Blinders, Blunders, and Wars analyzes eight historical examples of strategic blunders regarding war and peace and four examples of decisions that turned out well, and then applies those lessons to the current Sino-American case